Hak Substitusi Pada Pemberian Kuasa Beserta Tanggung Jawab Hukumnya - Nurun Ainuddin (Jatiswara, 2015)
This study is a literature that studies conducted only based on written work, including the results of both studies have not been well publicized. This study does not directly go into the field in search of data sources and can be done at home, the library and other places. The purpose of this study was to mengetahi more deeply about empowering substitutions which means the person who accepts the power of appoint another person to replace him in a legal action with consequences that are tailored to deal with and to know the limits of responsibility for authorizing and authorized substitution. As for the results to be achieved in this study is the extent to which the legal responsibility of the proxy substitutes the power delegated to him that the original authorizer not feel disappointed premises performance. The conclusion of this study is the original authorizer has the right to request information and the responsibility of the receiving power of substitution to the power that has been given.